Innovative strengthening of RC columns using a layer of a fibre reinforced concrete - Peter Koteš; Martin Vavruš; Wioletta Raczkiewicz (Acta Polytechnica CTU Proceedings, 2022)
Reinforced concrete structures that are influenced by degradation, overloading, the thawing and freezing cycles, abrasive damage and corrosion of reinforcement, should be repaired or strengthened. Each of those mentioned situations lead to decreasing the load-carrying capacity of the construction. The damage of a structure or its member causes exceeding the serviceability limit states and ultimate limit states. For this reason, for further use of the structures, they have to be strengthened to increase the load-carrying capacity and to extend the remaining lifetime. A new method for strengthening the vertical members, e.g., columns, is using the fibre reinforced concrete layer and its increased tensile strength in comparison to common RC concrete. This article deals with the theoretical design of dimensioning the columns using a layer of fibre concrete around a column (wrapping). In this case, it is necessary to calculate the residual strength of fibre concrete, which is a crucial factor for the tensile strength of the element.